Motif on Apin mat ethnic Murut / Norayni Mohd Basran - Mohd Basran, Norayni (2019)
This paper contains an analysis of symmetry for Apin mat created in the ethnic Murut. Wicker mat ethnic murut called mat as Apin or Lantungan is a term used by Murut Tahol referring to woven mats. Normally, Lantungan are named the types of rattan used to weave. There are three types of weaving, Apin Lantungan, Lantungan Ulia, Lantungan Puaran. These designs are very distinctive in term of motives and pattern. Apin mat are used as decorative motifs for woven Silaung, woven mat, woven lalandau woven tavil and woven buyong for using live. The basic woven objects are considered plain without kelarai. Apin mat design in a woven mat requires creativity and mathematical skills of the wover to ensure the consistency in design. Therefore, motive and pattern is used as a method to discover the role of symmetry in the formation of Apin mati design. There are ten selected Kelarai patterns used in this analysis. The analysis divides the Apin mat patterns into which are based on the symmetry line, 45°, 90°, 180° and 360°.